Thermal pleasure in built environments: alliesthesia in different thermoregulatory zones. Issue 1 (2nd January 2016) - Parkinson, Thomas; de Dear, Richard; Candido, Christhina
Abstract : The principle of thermal alliesthesia indicates that the hedonic character of a thermal environment is determined as much by the general state of the subject as by the environment itself. An environmental stimulus that offsets or counters a thermoregulatory load error will be pleasantly perceived, and vice versa. Extant empirical evidence supporting thermal alliesthesia only exists for instances of core temperature deviation. Yet the reconciliation of alliesthesia with contemporary neurophysiological discourse (in the previous paper in this series) renders the concept directly relevant to everyday experiences in built environments where core temperature rarely deviates from neutral values. New experimental data are presented that explore alliesthesia in non-steady-state conditions across three different physiological states: thermoneutral; the upper and lower fringes of the thermoneutral zone; and mild excursions into the sweating and shivering regulatory zones. Thirteen human subjects evaluated the hedonic tone of a sequence of temperature step-changes and ramps. It was found that the psychophysiological principle of thermal alliesthesia operates within the thermoneutral zone, making it equally relevant to quotidian indoor environments as it is to the extremes found in traditional physiological research. Non-steady-state built environments can potentially offer spatial alliesthesia through carefully managed contrasts between local and mean skin temperature trends. Transitional zones are suggested as design solutions.